1981
DOI: 10.1103/physrevc.23.700
|View full text |Cite
|
Sign up to set email alerts
|

Charged-particle emission in reactions of 15-MeV neutrons withY89,Zr

Abstract: Charged-particle emission cross sections, spectra, and angular distributions have been measured for targets of "Y, Zr, and """ Mo bombarded with 14.8-MeV neutrons. A magnetic quadrupole spectrometer served to detect the charged particles. Evidence for both statistical and pre-equilibrium reaction mechanisms was found in the proton, deuteron, and alpha-particle emission. The cross sections and spectra are compared with calculations based on these reaction models. targets. Hauser-Feshbach and hybrid pre-equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 16 publications
7
32
1
Order By: Relevance
“…8-9). The good agreement of the STAPRE-H calculations using the given preformation probabilities with the data of Haight et al [62] is shown in Figs. 5-7.…”
Section: The (N 2n) Reactionssupporting
confidence: 69%
See 4 more Smart Citations
“…8-9). The good agreement of the STAPRE-H calculations using the given preformation probabilities with the data of Haight et al [62] is shown in Figs. 5-7.…”
Section: The (N 2n) Reactionssupporting
confidence: 69%
“…Around 14.5 MeV, this database is complemented by emission spectra [62]. The experimental data below 13 MeV have been measured mostly at FZ Jülich, and to some extent at Debrecen, but in general, the low-energy region has not been investigated as well as the higher-energy region.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations